SOCIAL CONSTRUCTION OF RESPONSIBILITY IN SIRI POLYGAMY IN MADURA - Adiyono; Rudi Hermawan; Agustina Kumala Dewi Sholihah; Hawa Gazani; Ach. Mus’if (Familia: Jurnal Hukum Keluarga, 2026)
This study examined siri polygamy (unregistered polygamy) in Madurese society, focusing on second and third wives and community leaders. It investigated the husband's "seriousness" as justification and assesses rights protection for women and children in these unregistered marriage. The analysis revealed tensions between tradition and state law, offering insights into contemporary Indonesian polygamous families. This study used qualitative study by applied a sociologicallegal approach, employing a case study method with in-depth interviews of six women in polygamous relationships in Madura. Conclusions: First, the husband's motive of "seriousness" in practicing siri polygamy was  locally interpreted as a sign of commitment through the husband's provision to his secret wife of a permanent residence, regular financial support, and assurance of a secure future for her and their children, whereas temporary housing tends to raise suspicions about the husband's long-term commitment. Second, the Madurese community views the intention behind serious "e kabenthal patheh" siri polygamy a sincere intention for religious devotion and a desire to live together as being demonstrated by those who provide permanent housing and regular monthly financial support. Third, most women agree to siri polygamy because their husbands give them high hopes of living together permanently, though these hopes sometimes fall short of their expectations.